A JOURNEY TO MATURITY IN A WALK TO REMEMBER BY NICHOLAS SPARKS - Adisti Khairunnisa; Bachrudin Musthafa; Nita Novianti (Universitas Muhammadiyah Makassar, 2019)
This study aims to examine the journey to maturity of the main character, Landon Carter, in A Walk to Remember by Nicholas Sparks, by analyzing the literary elements that construct it. Employing a textual analysis method, this study is framed within Allport’s (1961) theory of maturity, and to discuss the analysis, Bean and Moni’s (2003) theory of young adult literature is also employed. The findings show that Landon’s journey to maturity is depicted mostly through the use of one literary element, namely characterization peculiar to Reams’ (2015). Based on Allport’s (1961) general criteria of maturity, throughout the story, Landon shows six types of maturity: (1) extension of the sense of self, (2) warm relatedness of self to others, (3) emotional security, (4) realistic perception of skills, (5) self-insight, and (6) unifying philosophy of life, and three types of immaturity: (1) an ego-centric sense of self, (2) emotional insecurity, and (3) lack of self-insight. Based on the analysis, several moral values can be obtained by young adult readers with different perspectives from reading Landon’s journey to maturity, such as the importance of being mature and the struggles of attaining maturity.